Inventory Management Analysis in Supporting Production Sustainability: A Case Study of a Catering MSME in South Tangerang - Anton PW Nomleni; Wijil Nugroho; Ribka Gracia; Angel Andromeda Persius (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
The rapid growth of MSMEs (Micro, Small, and Medium Enterprises) in South Tangerang City, projected to reach 114,000 businesses by 2024, demonstrates the sector’s significant contribution to the local economy, particularly in culinary fields such as catering services. This study aims to analyze inventory management practices among MSME catering businesses in South Tangerang (UCTS) to support production continuity and enhance customer satisfaction. Proper inventory management is crucial for maintaining raw material quality, reducing storage costs, and ensuring timely service. Employing a qualitative approach with a case study design, the research involved four purposively selected UCTS business owners. Data collection techniques included in-depth interviews, direct observations, and documentation. Findings indicate that inventory is managed selectively based on the nature of the raw materials. Perishable goods such as cassava, chicken, fish, and shrimp are procured daily through long-term relationships with trusted suppliers, while durable items like rice, cooking oil, and spices are stored in limited quantities to anticipate large orders. The success of inventory management is supported by strong communication and mutual trust between business owners and suppliers. The study reveals that effective inventory control helps prevent stockouts, minimize waste, and ensure business continuity. The findings conclude that UCTS businesses have implemented efficient and adaptive inventory strategies aligned with their operational needs. The implications of this study include cost efficiency, smoother production processes, reduced risk of spoilage or obsolescence, enhanced competitiveness, and stronger supply chain relationships. This research is limited to members of the UCTS catering community in South Tangerang and does not include MSMEs from other communities or sectors.